2015
DOI: 10.1186/s12866-015-0439-z
|View full text |Cite
|
Sign up to set email alerts
|

Coaggregation and biofilm growth of Granulicatella spp. with Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans

Abstract: BackgroundMembers of fastidious Granulicatella and Aggregatibacter genera belong to normal oral flora bacteria that can cause serious infections, such as infective endocarditis. Aggregatibacter actinomycetemcomitans has long been implicated in aggressive periodontitis, whereas DNA-based methods only recently showed an association between Granulicatella spp. and dental diseases. As bacterial coaggregation is a key phenomenon in the development of oral and nonoral multispecies bacterial communities it would be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 62 publications
(81 reference statements)
7
41
0
1
Order By: Relevance
“…Biofilm formation by Granulicatella spp. was reported by Karched et al [23]. In agreement with the results obtained in this study, using plastic plate adherent assay with crystal violet stain, it was revealed that G. adiacens possesses the ability to form biofilms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Biofilm formation by Granulicatella spp. was reported by Karched et al [23]. In agreement with the results obtained in this study, using plastic plate adherent assay with crystal violet stain, it was revealed that G. adiacens possesses the ability to form biofilms.…”
Section: Discussionsupporting
confidence: 93%
“…Then, 200 µL of ethanol (95%) was added to each well, and the plate was incubated at room temperature for 10 min. Then, 100 µL sample from each well were used to measure the optical densities at 590 nm using a microplate reader (Molecular Devices LLC, Tokyo, Japan) according to the method described by Karched et al [23]. For performing scanning electron microscopy, G. adiacens and A. defectiva strains were grown in THB at 37°C for 24 h. After washing with PBS, the cells were fixed in an equal volume of 2.5% glutaraldehyde in PBS for 30 min.…”
Section: Production Of Eps Biofilmmentioning
confidence: 99%
“…Of note, coaggregation assays were carried out using planktonic cultures and aimed to assess the possible mechanism behind the development of bacterial biofilms (Rickard et al, 2003). However, it has been reported that there is not always a direct relation between coaggregation and biofilm formation (Karched et al, 2015). In brief, 500 µL of G. vaginalis (10 7 CFU/mL) was combined with 500 µL of A. vaginae (10 7 CFU/mL) in 24-well plates (Thermo Fisher Scientific) and incubated for 4 h, at 37 • C, under anaerobic conditions.…”
Section: Coaggregation Assaysmentioning
confidence: 99%
“…The congregation of Granulicatella spp. with Aggregatibacter actinomycetemcomitans [48] has been positively correlated to periodontitis [49], as well as serious infections outside of the oral cavity, such as infective endocarditis [50]. Veillonella is a genus of Gram-negative anaerobic bacteria mainly found in the oral and gastrointestinal tracts.…”
Section: Discussionmentioning
confidence: 99%